"You can't go back to holding hands." Reading Judy Blume's Forever in the #MeToo Era - Jenna Spiering; Kate Kedley (University of Oklahoma Libraries, 2019)
Judy Blume's Forever is a cultural artifact that gives readers a historical look at society's attitudes about sex and sexuality at the time of publication in 1975. However, in the #MeToo era, Blume's text is poised for new analysis in light of important conversations and concerns about sex, sexuality, and consent. In this article, Critical Youth Studies and Queer Theory are used to explore the ways in which young readers can critically engage with Blume's novel and questions about virginity, sex, sexuality, and consent associated with the #MeToo movement.